Epithelium-derived miR-204 inhibits corneal neovascularization. (February 2018) - Zhang, Xiaoping; Di, Guohu; Dong, Muchen; Qu, Mingli; Zhao, Xiaowen; Duan, Haoyun; Hu, Xiaoli; Liu, Ting; Zhou, Qingjun; Shi, Weiyun
Abstract: MicroRNA-204 (miR-204) is highly expressed in cornea, here we explored the role and mechanism of miR-204 in corneal neovascularization (CNV). Mouse CNV was induced by intrastromal placement of suture in BALB/c mice with the subconjunctival injection of miR-204 agomir or negative control. Human primary limbal epithelial cells (LECs) and immortalized microvascular endothelial cells (HMECs) were used to evaluate the expression changes and anti-angiogenic effects of miR-204 under biomechanical stress (BS). The expression and localization of miR-204, vascular endothelial growth factor (VEGF) and their receptors were detected by quantitative real-time PCR, in situ hybridization, immunohistochemistry and Western blot. The results showed that miR-204 expression was mainly localized in epithelium and down-expressed in vascularized cornea. Subconjunctival injection of miR-204 agomir inhibited CNV and reduced the expression of VEGF and VEGF receptor 2. Similarly, miR-204 overexpression attenuated the increased expression of VEGF by biomechanical stress in LECs, and suppressed the proliferation, migration, and tube formation of HMECs. These novel findings indicate that epithelium-derived miR-204 inhibits suture-induced CNV through regulating VEGF and VEGF receptor 2. Highlights: MiR-204 was down-expressed in corneal epithelium with neovascularization. Exogenous miR-204 suppressed corneal neovascularization. MiR-204 suppressed VEGF-A and VEGFR2 expression. MiR-204 attenuated biomechanical stress-induced VEGF-A expression in HMECs.